First supplement to the lichen checklist of South Africa - Ahti, Teuvo; Mayrhofer, Helmut; Schultz, Matthias; Tehler, Anders; Fryday, Alan (African Biodiversity & Conservation, 2016)
Details are given of errors and additions to the recently published checklist of lichens reported from South Africa (Fryday 2015). The overall number of taxa reported from South Africa is increased by one, to 1751.